Effect of Funneliformis mosseae and Cu Additives on the Astragalus sinicus Root Growth and Cd Uptake Under the Modeled Conditions - Yuxin Li; Rui Cai; Jindian Hu; Hongling Liu; Xiancan Zhu (Microorganisms)
Cadmium (Cd) contamination in soil poses a serious threat to plant growth and productivity, while arbuscular mycorrhizal (AM) fungi play a vital role in enhancing plant growth, improving tolerance to heavy metals, and restoring polluted ecosystems. To enhance the tolerance of Astragalus sinicus to Cd stress, a pot experiment was conducted to investigate the effects of inoculation and copper (Cu) addition on growth, Cd accumulation, and translocation under Cd-stressed soil conditions. The results showed that Cd inhibited the root growth of A. sinicus, and AM fungi inoculation and Cu + AM significantly increased root biomass and root volume (p < 0.05). Under Cd stress, AM fungi inoculation reduced Cd concentration by 72.40% in the shoots, while it increased by 92.69% in the roots. Both AM fungi inoculation and Cu + AM enhanced Cd uptake in the roots, while inhibiting Cd translocation to the shoots. After the application of Cu and inoculation with AM fungi, the roots have a strong absorption and enrichment ability for Cd; the bioconcentration factor of Cd in the roots of A. sinicus reached 1018.59% and 366.08%, respectively. Cu + AM increased the enrichment of Cd in the roots and restricted its translocation to the shoots. Moreover, the combination of AM fungi inoculation and Cu addition significantly increased soluble sugar (by 77.29%) and proline contents (by 445.62%) and reduced CAT activity (by 74.67%) under Cd stress. In summary, both Cu addition and AM fungi inoculation promoted the growth of A. sinicus under Cd stress, improved its physiological metabolism, and reduced Cd content in the soil, with the combined Cu and AM fungi treatment showing the most significant effect.